2007
DOI: 10.1111/j.1525-1438.2007.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, diabetes, and other factors in relation to survival after endometrial cancer diagnosis

Abstract: Endogenous and exogenous sources of estrogen and characteristics altering these hormone levels have been related to endometrial cancer risk; however, their relationship to survival following diagnosis is less clear. In a population-based study, we examined whether mortality after endometrial cancer diagnosis was affected by prediagnosis obesity, diabetes, smoking, oral contraceptive use, parity, or postmenopausal hormone (PMH) use. Eligible women, aged 40-79 years, diagnosed from 1991-1994 with incident invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 25 publications
2
89
1
2
Order By: Relevance
“…Fewer studies have reported on disease-specific survival: Folsom and colleagues (16) found poorer survival for those with diabetes, as we did, whereas Chia and colleagues (17) found no association.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Fewer studies have reported on disease-specific survival: Folsom and colleagues (16) found poorer survival for those with diabetes, as we did, whereas Chia and colleagues (17) found no association.…”
Section: Discussionmentioning
confidence: 51%
“…In particular, diabetes and hypertension are more prevalent in blacks than in whites (13) and some studies suggest that presence of diabetes is associated with poorer survival in women with endometrial cancer (14)(15)(16)(17). We used the population-based SEER-Medicare database to assess the influence of medical conditions on overall and disease-specific survival in older women with endometrial cancer and to determine whether these factors explained part of the disparity in outcome between blacks and whites.…”
Section: Introductionmentioning
confidence: 99%
“…The few findings that are available are inconsistent with worse survival reported for diabetic compared to non-diabetic patients with pancreatic [1], liver [2], breast [3], colorectal [4], and endometrial cancers [5,6], while other studies have shown no association between diabetes and survival for colorectal [7] and lung cancer patients [8]. One study found that diabetic patients with various cancers had better survival than non-diabetic patients with these cancers [9].…”
Section: Introductionmentioning
confidence: 93%
“…Recently, interest in the anticancer properties of metformin has emerged as epidemiologic studies in patients with breast and prostate cancer have shown a survival advantage in patients taking this medication [55][56][57][58]. Additionally, patients with endometrial cancer who are obese or have diabetes have been shown to have compromised survival and increased recurrence rates [59]. This adverse oncologic outcome associated with metabolic syndrome in patients with endometrial cancer may be a direct result of the metabolic and endocrine effects of obesity.…”
Section: Toxicities Associated With Pi3k Mtor and Akt Inhibitors In Enmentioning
confidence: 99%